Factors influencing generation z's green investment interest - Nilasari, Priyanti Dewi; Prajawati, Maretha Ika; S, Basir (Journal of Multiperspectives on Accounting Literature, 2025)
Purpose: Green investment interest emerged as a response to increasing carbon emissions around the world, including in Indonesia. This study aims to examine the factors that influence Generation Z's green investment interest, using an extended framework based on the theory of planned behavior. Methodology/approach: This study used Cochran's Formula in determining the research sample. Data were collected using questionnaires distributed to 100 students of public universities in Malang City who have made green investments. Data were tested using Partial Least Square Structural Equation Modeling (PLS-SEM). This study explores how attitudes, subjective norms, behavioral control, and green investment knowledge affect Generation Z's interest in green investment. Findings: The results of this study indicate that there is a significant positive influence between attitude, behavioral control, and green investment knowledge on Generation Z's green investment interest. However, subjective norms have an insignificant positive effect on Generation Z's green investment interest. Practical implications: In this conclusion, the study suggests that stakeholders providers can tailor green investment products and communication strategies to align with Generation Z's attitudes and knowledge levels. Originality/value: This study offers the valuable insight with use of an expanded Theory of Planned Behavior by including knowledge of green investments as a new variable. By presenting concrete data from real green investors, it challenges preconceived notions and shows that subjective norms have no discernible impact. The study's focus on green investment behavior is distinctive and in line with worldwide sustainability trends.